Adhesive Stalks of Diatom Didymosphenia geminata as a Novel Biological Adsorbent for Hazardous Metals Removal. Issue 11 (16th October 2017) - Wysokowski, Marcin; Bartczak, Przemysław; Żółtowska‐Aksamitowska, Sonia; Chudzińska, Agata; Piasecki, Adam; Langer, Enrico; Bazhenov, Vasilii V.; Petrenko, Iaroslav; Noga, Teresa; Stelling, Allison L.; Ehrlich, Hermann; Jesionowski, Teofil
Abstract : The application of biomass derived from the nuisance fresh‐water diatom species Didymosphenia geminata toward the adsorption and removal of heavy‐metal ions from water is reported. The cell‐free polysaccharide‐based stalks of these diatoms are used as adsorbents to remove harmful metal ions: Pb(II), Ni(II), and Cd(II). Detailed analyses of the adsorption kinetics using both pseudo‐first‐order model and pseudo‐second‐order models are performed. The results show a strong correspondence to a pseudo‐second‐order kinetic model. The Langmuir and Freundlich models are used to describe the adsorption isotherms. The correlation coefficients ( r 2 ) of the Langmuir model are equal to 0.994 (Pb 2+ ), 0.995 (Cd 2+ ), and 0.995 (Ni 2+ ), and the r 2 for the Freundlich model are equal to 0.991 (Pb 2+ ), 0.991 (Cd 2+ ), and 0.987 (Ni 2+ ). The experimental data for all metal ions strongly support the Langmuir isotherm model. It is shown that stalks of D. geminata exhibit exceptional sorption capacity ( q m ) for Pb(II) ions of 175.48 mg g −1 . Additionally, a high sorption capacity for Cd(II) (145.86 mg g −1 ), and Ni(II) (130.27 mg g −1 ) is observed. The thermodynamic aspects of the adsorption process of selected metal ions are also discussed. Preliminary tests investigating applications of D. geminata stalks for sewage purification from galvanic industry and battery and accumulator production were performed. These comprehensive studies show that D. geminata can be robustly applied for the removal of harmful metal ions from wastewater. Abstract : Didymosphenia geminata has emerged as a nuisance specimen in river systems around the world. Herein, the practical application of stalks isolated from this diatom is reported for the first time. The experiments prove that polysaccharide‐based stalks can be used as a low‐cost sorbent for the removal of harmful metal ions from industrial wastewater.